Mechanistic Drivers of Müllerian Duct Development and Differentiation Into the Oviduct - Santana Gonzalez, Laura; Rota, Ioanna A.; Artibani, Mara; Morotti, Matteo; Hu, Zhiyuan; Wietek, Nina; Alsaadi, Abdulkhaliq; Albukhari, Ashwag; Sauka-Spengler, Tatjana; Ahmed, Ahmed A. (Frontiers in Cell and Developmental Biology, 2021)
The conduits of life; the animal oviducts and human fallopian tubes are of paramount importance for reproduction in amniotes. They connect the ovary with the uterus and are essential for fertility as they provide the appropriate environment for gamete maintenance, fertilisation and preimplantation embryonic development. However, some of the most serious pathologies, such as ectopic pregnancy, malignancy and severe infections, occur in the oviducts. They can have drastic effects on fertility, and some are even life-threatening. Despite the crucial importance of the oviducts in life, relatively little is known about the molecular drivers underpinning the embryonic development of their precursor structures, the Müllerian ducts, and their successive differentiation and maturation. The earliest sign of Müllerian duct formation is the appearance of the thickening of the anterior mesonephric coelomic epithelium to form a placode of progenitor cells. Distinct populations of progenitor cells subsequently give rise to the luminal and mesenchymal cell layers of the Müllerian duct. In a pivotal step in early Müllerian duct development, one subset of progenitor cells undergoes partial epithelial-mesenchymal transition (pEMT), differentiating into luminal cells, and another subset undergoes complete EMT to become mesenchymal cells. Subsequently, pEMT is reversed to generate epithelial cells lining the fully formed Müllerian lumen, and some of these epithelial cells will further specialise into the oviduct epithelial subtypes. This review highlights the key established molecular and genetic determinants of the processes involved in Müllerian duct development and the differentiation of its upper segment into oviducts. Furthermore, an extensive genome-wide survey of mouse knockout lines displaying Müllerian or oviduct phenotypes was undertaken. In addition to widely established genetic determinants of Müllerian duct development, our search has identified surprising associations between loss-of-function of several genes and high penetrance abnormalities in the Müllerian duct and/or oviducts. Remarkably, these associations have not been investigated in any detail. Finally, we discuss future directions for research on Müllerian duct development and oviducts.